Ostéochondronécroses articulaires - Silvia Boccone; Rosa Boano; Enzo Fulcheri; Emma Rabino Massa (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
As part of investigations carried out in the Dauphiné region of France during the past few years, ancient human remains discovered in the Church of Puy-Saint-Pierre in Briançon and in the church of La Salle les Alpes, 6-7 km from Briançon (Haute-Alpes), have undergone anthropological and palaeopathological studies.In our studies of the medieval and modern samples, we were able to observe a significant frequency of bone and joint lesions. By their morphology and location, they can be attributed to osteochondronecrosis. Osteochondronecrosis is a generic term which defines lesions of vascular origin in the joints, characterized by localized cartilage detachment and associated with or subsequent to localized subchondral bone necrosis. The lesions differ in appearance, depending on the stage of development. Generically defined by some authors as ostechondritis dissecans, osteochondrosis includes lesions that can be very different aetiologically (post-traumatic, genetic, arthritic/degenerative).